Psychological Drivers of Alternative Fuel Vehicles' Adoption and Ecologically Responsible Use. (29th December 2021) - Saleem, Muhammad Abid; Ali, Rao Akmal; Shah, Syed Noman Ali; Zahra, Sadaf; Hafeez, Muhammad Haroon; Nguyen, Ninh
Abstract : Environmental problems caused by global warming are becoming alarming with every passing day. To curb greenhouse gas (GhG) emissions, promoting alternative fuel vehicles (AFVs) and sustainable transport mode choices is critical. This study explores the predictors of eco-social purchase, use, and conservation intentions in a developing country by employing an extended model of the theory of planned behaviour (TPB). Using a self-administered survey technique, data were collected from a nationally representative sample of 1372 customers of three leading automobile manufacturers from eight big cities of Pakistan. Partial Least Squares Structural Equation Modelling (PLS-SEM) was applied to test the measurement and structural models. Results showed that the extended model of TPB received support in the context of Pakistani culture and for the targeted behaviours related to eco-social purchase, use, and conservation intentions concerning AFVs. Implications for marketers and theoretical contribution are discussed at the end.